Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1.=(x-2)(x 2+2x+7)+2(x-2)(x+2)-5(x-2) = 0
=>(x-2)(x 2+2x+7+2x+4-5) = 0
=>(x-2)(x 2+4x+6) = 0
Mà x 2+4x+6 (E Z)
=> x 2+4x+6 > 0
Vậy (x-2)=0 => x = 2
\(\dfrac{x^2+4x+6}{x+2}+\dfrac{x^2+16x+72}{x+8}=\dfrac{x^2+8x+20}{x+4}+\dfrac{x^2+12x+42}{x+6}\)ĐKXĐ là \(x\ne-2;x\ne-8;x\ne-4;x\ne-6\)
\(\dfrac{x^2+4x+4+2}{x+2}+\dfrac{x^2+16x+64+8}{x+8}=\dfrac{x^2+8x+16+4}{x+4}+\dfrac{x^2+12x+36+6}{x+6}\)\(\Leftrightarrow\dfrac{\left(x+2\right)^2+2}{x+2}+\dfrac{\left(x+8\right)^2+8}{x+8}=\dfrac{\left(x+4\right)^2+4}{x+4}+\dfrac{\left(x+6\right)^2+6}{x+6}\)
\(\Leftrightarrow x+2+\dfrac{2}{x+2}+x+8+\dfrac{8}{x+8}=x+4+\dfrac{4}{x+4}+x+6+\dfrac{6}{x+6}\)
\(\Leftrightarrow\dfrac{2}{x+2}+\dfrac{8}{x+8}=\dfrac{4}{x+4}+\dfrac{6}{x+6}\)
\(\Leftrightarrow\left(\dfrac{2}{x+2}-1\right)+\left(\dfrac{8}{x+8}-1\right)=\left(\dfrac{4}{x+4}-1\right)+\left(\dfrac{6}{x+6}-1\right)\)\(\Leftrightarrow\dfrac{-x}{x+2}+\dfrac{-x}{x+8}=\dfrac{-x}{x+4}+\dfrac{-x}{x+6}\)
\(\Leftrightarrow\dfrac{x}{x+2}+\dfrac{x}{x+8}-\dfrac{x}{x+4}-\dfrac{x}{x+6}=0\)
\(\Leftrightarrow x\left(\dfrac{1}{x+2}+\dfrac{1}{x+8}-\dfrac{1}{x+4}-\dfrac{1}{x+6}\right)=0\)
Do \(\dfrac{1}{x+2}+\dfrac{1}{x+8}-\dfrac{1}{x+4}-\dfrac{1}{x+6}\ne0\)
=> x=0
Vậy ....
a) \(\left(x^2+2x-2\right)\left(x^2+2x+3\right)=6\)
Đặt \(x^2+2x=a\)
\(pt\Leftrightarrow\left(a-2\right)\left(a+3\right)=6\)
\(\Leftrightarrow a^2+a-6=6\)
\(\Leftrightarrow a^2+a-12=0\)
\(\Leftrightarrow a^2+3a-4a-12=0\)
\(\Leftrightarrow a\left(a+3\right)-4\left(a+3\right)=0\)
\(\Leftrightarrow\left(a-4\right)\left(a+3\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}a-4=0\\a+3=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}a=4\\a=-3\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x^2+2x=4\\x^2+2x=-3\end{cases}}\)
\(Th1:x^2+2x=4\Leftrightarrow x^2+2x-4=0\)
\(\cdot\Delta=2+4.4=18\)
pt có 2 nghiệm \(x_1=\frac{-2+\sqrt{18}}{2}\);\(x_2=\frac{-2-\sqrt{18}}{2}\)
\(Th1:x^2+2x=-3\Leftrightarrow x^2+2x+3=0\)
\(\cdot\Delta=2-4.3=-10< 0\)
Vậy pt này không có nghiệm
Vậy \(x_1=\frac{-2+\sqrt{18}}{2}\);\(x_2=\frac{-2-\sqrt{18}}{2}\)
b) \(\left(x^2-4x+6\right)\left(x^2-4x+8\right)=8\)
Đặt \(x^2-4x=t\)
\(pt\Leftrightarrow\left(t+6\right)\left(t+8\right)=8\)
\(\Leftrightarrow t^2+14x+48=8\)
\(\Leftrightarrow t^2+14x+40=0\)
\(\Delta=14^2-4.40=36,\sqrt{\Delta}=6\)
pt có 2 nghiệm: \(t_1=\frac{-14+6}{2}=-4\);\(t_2=\frac{-14-6}{2}=-10\)
\(\Leftrightarrow\orbr{\begin{cases}x^2-4x=-4\\x^2-4x=-10\end{cases}}\)
\(TH1:x^2-4x=-4\Leftrightarrow\left(x-2\right)^2=0\Leftrightarrow x-2=0\)
\(\Leftrightarrow x=2\)
\(TH2:x^2-4x=-10\Leftrightarrow x^2-4x+10=0\)
\(\Delta=\left(-4\right)^2-4.10=-24< 0\)
Vậy pt này không có nghiệm
Vậy x = 2
1) \(x^2+x-2=0\)
\(\Leftrightarrow x^2+2x-x-2=0\)
\(\Leftrightarrow x\left(x+2\right)-\left(x+2\right)=0\)
\(\Leftrightarrow\left(x+2\right)\left(x-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=-2\\x=1\end{cases}}\)
2) \(x^2+2x-3=0\)
\(\Leftrightarrow x^2+3x-x-3=0\)
\(\Leftrightarrow x\left(x+3\right)-\left(x+3\right)=0\)
\(\Leftrightarrow\left(x+3\right)\left(x-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=-3\\x=1\end{cases}}\)
3) \(x^2-x-6=0\)
\(\Leftrightarrow x^2-3x+2x-6=0\)
\(\Leftrightarrow x\left(x-3\right)+2\left(x-3\right)=0\)
\(\Leftrightarrow\left(x-3\right)\left(x+2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=3\\x=-2\end{cases}}\)
4) \(x^2+x-6=0\)
\(\Leftrightarrow x^2+3x-2x-6=0\)
\(\Leftrightarrow x\left(x+3\right)-2\left(x+3\right)=0\)
\(\Leftrightarrow\left(x+3\right)\left(x-2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=-3\\x=2\end{cases}}\)
5) \(2x^2-x-6=0\)
\(\Leftrightarrow2x^2-4x+3x-6=0\)
\(\Leftrightarrow2x\left(x-2\right)+3\left(x-2\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(2x+3\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=2\\x=-\frac{3}{2}\end{cases}}\)
b, ( x2 + x ) ( x2 + x + 1 )=6
=> ( x2 + x ) ( x2 + x + 1) - 6 = 0
=> ( x - 1 ) ( x + 2 ) ( x2 + x +3 ) = 0
=> x - 1= 0 => x= 1
=> x + 2 = 0 => x = -2
=> x2 + x + 3 = 0 => 12 - 4 ( 1.3 ) = -11 ( vô lí )
Vậy x = 1; x= -2
a) \(2x^3-x^2+3x+6=0\)
\(\left(2x^3-x^2\right)+\left(3x+6\right)=0\)
\(x^2\left(2-x\right)-3\left(2-x\right)=0\)
\(\left(x^2-3\right)\left(2-x\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x^2-3=0\\2-x=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=\sqrt{3}\\x=2\end{cases}}\)\(\)
vậy \(\orbr{\begin{cases}x=\sqrt{3}\\x=2\end{cases}}\)
\(\left(x+8\right)\left(x+6\right)-x^2=104\)
\(\Rightarrow x^2+14x+48-x^2=104\)
\(\Rightarrow14x=56\Rightarrow x=4\)
\(\Rightarrow x^2+14x+48-x^2=104\\ \Rightarrow14x=56\\ \Rightarrow x=4\)